Uwarunkowania prawne i polityczne a konkurencyjność branży elektroenergetycznej OZE w Polsce i w Niemczech - Staliński, Adam (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The aim of this paper is to analyse how legal and political conditions in Poland and Germany affect the competitiveness of renewable energy (RES) production. The analysis also includes the most important competitive source of energy in both countries, namely coal. An attempt to assess the influence of governments on the RES sector by influencing carbon-based energy was also made. The framework of this analysis is expanded diamond of M. E. Porter's competitive advantage of nations, although its scope was limited to the governmental factor and its influence on the other components of the model. The analysis shows great importance of legal and political conditions for the competitiveness of RES in both countries, including enormous impact of hidden support for coal, and indicates disadvantages of the methods of RES subsidising.